Construction of Ultrathin Layered MXene-TiN Heterostructure Enabling Favorable Catalytic Ability for High-Areal-Capacity Lithium–Sulfur Batteries - Wang, Hao; Cui, Zhe; He, Shu‑Ang; Zhu, Jinqi; Luo, Wei; Liu, Qian; Zou, Rujia (Nano-Micro Letters, 2022)
Catalysis has been regarded as an effective strategy to mitigate sluggish reaction kinetics and serious shuttle effect of Li–S batteries. Herein, a spherical structure consists of ultrathin layered Ti3C2Tx-TiN heterostructures (MX-TiN) through in-situ nitridation method is reported. Through controllable nitridation, highly conductive TiN layer grew on the surface and close coupled with interior MXene to form unique 2D heterostructures. The ultrathin heterostructure with only several nanometers in thickness enables outstanding ability to shorten electrons diffusion distance during electrochemical reactions and enlarge active surface with abundant adsorptive and catalytic sites. Moreover, the (001) surface of TiN is dominated by metallic Ti–3d states, which ensures fast transmitting electrons from high conductive MX-TiN matrix and thus guarantees efficient catalytic performance. Calculations and experiments demonstrate that polysulfides are strongly immobilized on MX-TiN, meanwhile the bidirectional reaction kinetics are catalytically enhanced by reducing the conversion barrier between liquid LiPSs and solid Li2S2/Li2S. As a result, the S/MX-TiN cathode achieves excellent long-term cyclability with extremely low-capacity fading rate of 0.022% over 1000 cycles and remarkable areal capacity of 8.27 mAh cm−2 at high sulfur loading and lean electrolytes. Highlights: 1 An in-situ strategy to synthesize ultrathin two-dimensional MXene-TiN heterostructures and the ultrathin structure extremely shortens the electrons diffusion distance from catalysts to active sulfur species. 2 The heterostructure exhibits superior electronic structures to strongly capture the polysulfides and enhance bidirectional electrocatalytic ability between LiPSs and Li2S. 3 The advanced cathode achieves an excellent long-term cyclability with an extremely low-capacity fading rate of 0.022% over 1000 cycles and a remarkable areal capacity of 8.27 mAh cm−2 at high sulfur loading of 10.16 mg cm−2.